Dinamika Perdebatan “Syariat Islam” Dalam Historisasi Piagam Jakarta (Jakarta Charter) - Aini Shalihah; fahri Hozaini (As-Shahifah : Journal of Constitutional Law and Governance, 2022)
In the Indonesian context, we find the principle of Belief in One God, which is contained in the preamble to the 1945 Constitution. And the Jakarta Charter is part of the body of the constitution which has now been transformed into Pancasila. The dynamics of the Jakarta Charter still leaves a long-standing difference by photographing the 7 words "...with the obligation to carry out Islamic law for its adherents". This paper will examine the dynamics of the debate on "Islamic law" in the historicization of the Jakarta charter. The method used is normative law with a statutory, conceptual and historical approach. The result of this paper is that such national legal norms such as the Jakarta Charter are generally applicable to all citizens without exception. Therefore, the name or designation for such a national legal norm does not need to be mentioned or associated with the name of the norm of a particular religion which can lead to misunderstandings which can actually cause difficulties in efforts to enforce the legal norms in reality. Its official designation suffices as Indonesian National Law which is now based on Pancasila.